Effect of vacuum application on the physical, rheological and sensory characteristics of an artisanal ice cream. (30th December 2022) - Lomolino, Giovanna; De Iseppi, Alberto; Bravo, Stefano; Vegro, Mara; Marangon, Matteo; Crapisi, Antonella; Curioni, Andrea
Abstract : Four milk‐based ice cream samples were produced by heating (65°C) the ingredients at different pressures (0.5, 1.0 bar) and times (5, 30 min). Overrun, melting behaviour, particle size, viscosity and sensory analysis were conducted for each time/temperature combination. The 5‐min vacuum application resulted in a reduction of overrun and air bubbles size, whereas ice cream viscosity increased. Opposite outcomes were found for the sample treated with vacuum for 30 min, which also showed a significant fat globule size reduction (<3.0 μm). Sensory analysis revealed that the use of vacuum improved sweetness, milky and creamy sensations regardless the treatment times. Abstract : The application of vacuum during the heat treatment of the ice mixture affects the overall quality of the final ice cream.